Evidence of the influence of adsorption kinetics on the internal reorganization of polyelectrolyte multilayers - Guzmán, Eduardo (2011)
X-ray reflectivity and adsorption kinetics of two different polyelectrolyte multilayers have been studied for polyelectrolyte multilayers (PEMs) composed of poly(diallyldimethyl ammonium chloride) (PDADMAC) and poly(sodium 4-styrenesulfonate) (PSS) polyelectrolyte pair and of poly(allylamine hydrochloride) (PAH) and PSS. The two characteristic times that describe the adsorption kinetics were found to be related to the X-ray reflectivity results, and their dependence on the number of adsorbed layers is depends on the growth mechanisms (linear or superlinear) of the films. Therefore, it has been concluded that there is a correlation between the adsorption kinetics and the internal structure of the films. The time allowed for the adsorption of each polyelectrolyte controls the extension of the interdiffusion within the multilayer, and therefore whether the film is formed by stratified layers or it has a uniform structure except for the first and last layers. While the roughness of the (PDADMAC + PSS)n films strongly depends on the adsorption time, it is almost independent of it for the (PAH + PSS)n multilayer. This behavior correlates with that of the longest characteristic time of the adsorption kinetics.